Tumor location is a risk factor for lymph node metastasis in superficial Barrett’s adenocarcinoma - Yamada, Masayoshi; Oda, Ichiro; Tanaka, Hirohito; Abe, Seiichiro; Nonaka, Satoru; Suzuki, Haruhisa; Yoshinaga, Shigetaka; Kuchiba, Aya; Koyanagi, Kazuo; Igaki, Hiroyasu; Taniguchi, Hirokazu; Sekine, Shigeki; Saito, Yutaka; Tachimori, Yuji (Endoscopy International Open, 2017)
Background and study aims Endoscopic treatment is indicated for superficial Barrett’s adenocarcinoma (BA) with a negligible risk of lymph node metastasis (LNM). However, risk factors associated with LNM in superficial BA are still not well characterized. The aim of the current study was to clarify risk factors for LNM of superficial BA. Patients and methods A retrospective study was conducted in 87 consecutive patients with BA that was resected at National Cancer Center Hospital, Tokyo, Japan between 1990 and 2013. We assessed tumor size, macroscopic type, histological type, tumor depth of invasion, lymphovascular invasion and tumor location to analyze factors associated with LNM. Tumor location was classified into following 2 groups according to Siewert classification: 1) BA of the esophagogastric junction (EGJ-BA) as those having their center within 1 cm proximal from the EGJ; and 2) Esophageal-BA as those having their center at 1 cm or more proximal to the EGJ. EGJ was defined as distal end of the palisade vessels.Results LNM was detected in 10 (11 %) patients. Univariable analysis revealed that tumor size, tumor depth of invasion, histological type of mixed differentiated and undifferentiated-type adenocarcinoma, lymphovascular invasion and tumor location of esophageal-BA were significantly associated with LNM. Multivariable analysis revealed that tumor location of esophageal-BA [odds ratio 7.8 (95 %CI: 1.3 – 48.1)] was a potential risk factor for LNM. Conclusions The current study demonstrated that tumor location is a potential risk factor for LNM in BA. Therefore, indications for endoscopic treatment of esophageal-BA and EGJ-BA could be different.